2021
DOI: 10.1186/s12877-021-02455-9
|View full text |Cite
|
Sign up to set email alerts
|

Long sleep duration is associated with cognitive frailty among older community-dwelling adults: results from West China Health and Aging Trend study

Abstract: Objective To investigate the association between sleep duration and cognitive frailty among older adults dwelling in western China. Methods We used the baseline data from West China Health and Aging Trend (WCHAT) study. Sleep duration was classified as short sleep duration (< 6 h), normal sleep duration (6–8 h) and long sleep duration (≥ 9 h). Fried frailty criteria and Short Portable Mental Status Questionnaire were used to measure cognitive fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
1
16
1
Order By: Relevance
“…Poor sleep quality significantly mediates the association between frailty severity and cognitive outcomes ( 41 ). In addition, an important study investigated the association between nighttime sleep duration and cognitive frailty, and the results showed that long sleep duration (≥9 h) was significantly associated with high prevalence of cognitive frailty among community-dwelling Chinese aged 50 and older ( 25 ). It is impossible to effectively assess the sleep quality of individuals because nighttime sleep duration is only one dimension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor sleep quality significantly mediates the association between frailty severity and cognitive outcomes ( 41 ). In addition, an important study investigated the association between nighttime sleep duration and cognitive frailty, and the results showed that long sleep duration (≥9 h) was significantly associated with high prevalence of cognitive frailty among community-dwelling Chinese aged 50 and older ( 25 ). It is impossible to effectively assess the sleep quality of individuals because nighttime sleep duration is only one dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to previous study groups ( 25 , 32 ), our study divided the included participants into five groups according to physical frailty and cognitive function status: (1) robust group: neither had physical frailty, physical pre-frailty, nor cognitive impairment; (2) physical pre-frailty group: older adults with only physical pre-frailty and without cognitive impairment; (3) physical frailty group: older adults with only physical frailty and no cognitive impairment; (4) cognitive impairment group: older adults who only had cognitive impairment but neither had physical pre-frailty nor physical frailty; (5) cognitive frailty group: older adults with both cognitive impairment and physical pre-frailty or physical frailty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, a key consideration in addressing CF is to find the potential predictors. Some studies have reported several factors associated with CF [13][14][15]. However, these findings mainly came from cross-sectional studies, which cannot establish the cause-and-effect relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Previous prospective studies explored the associations between sleep behaviors at baseline and the subsequent frailty status. However, the effects of unhealthy sleep duration were still inconclusive [5][6][7]. A prospective study with a small sample reported the association between sleep difficulties and worsening frailty [8].…”
Section: Introductionmentioning
confidence: 99%